2019
DOI: 10.11604/pamj.2019.33.37.17606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on markers of bone turnover in ovariectomized rats

Abstract: Introduction Osteoporosis is characterized by low bone mass and density, as well as change in microarchitecture of bone tissue leading to decreased bone strength. In vitro research shows nicotine can increase osteoblast activity and proliferation, also suppress osteoclast activity. Therefore we explore nicotine anti-resorptive property by in vivo true experimental and randomized posttest only controlled group research that was conducted in 18-20 weeks old Rattus norvegicus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Eight studies observed a decreased quantity of exocytotic products and/or gene expression, whereas one noted an increase in proteoglycan deposition (Table 1). 5,8-35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies observed a decreased quantity of exocytotic products and/or gene expression, whereas one noted an increase in proteoglycan deposition (Table 1). 5,8-35…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, of the remaining studies, eight showed an increase in these mechanisms. For example, Sananta et al 12 in a ovariectomized rat biological study noted decreased osteoclast activity with the addition of low-dose nicotine 8 weeks postoophorectomy. These results likely correlated with the chronicity of the oophorectomy and the inhibiting gene expression effect of nicotine on osteocalcin.…”
Section: Discussionmentioning
confidence: 99%